THE EFFECT OF BUSINESS CAPITAL ASSISTANCE AND MENTORING ON MUSTAHIK WELFARE IN THE ZMART PROGRAM BY BAZNAS SOUTH SUMATERA: SALES TURNOVER AS AN INTERVENING VARIABLE - Amel, Ropini Amelia; Mismiwati; Rinol Sumantri (Journal of Economics and Development, 2025)
This study aims to analyze the effect of business capital assistance and business mentoring on the welfare of mustahik in the Zmart Program by BAZNAS of South Sumatra Province, with sales turnover as an intervening variable. This study uses a quantitative approach with a total sample of 50 mustahik respondents receiving Zmart assistance. Data collection was conducted using primary data through the distribution of questionnaires with a Likert scale, as well as qualitative interviews with program implementers. The data analysis technique used in this study is Structural Equation Modeling (SEM) with Partial Least Squares (PLS) through the SmartPLS 4.0 program. The results showed that: (1) Business capital assistance has no direct effect on the welfare of mustahik, (2) Business mentoring has a direct positive and significant effect on the welfare of mustahik, (3) Business capital assistance has no direct effect on sales turnover, (4) Business mentoring has a direct positive and significant effect on sales turnover, (5) Sales turnover has a direct positive and significant effect on the welfare of mustahik, (6) Sales turnover does not mediate the effect of business capital assistance on the welfare of mustahik, (7) Sales turnover mediates the effect of business mentoring on the welfare of mustahik. This study also evaluates the implementation of the Zmart Program through the lens of maqāṣid al-sharī‘ah according to Imām al-Ghazālī, which includes the preservation of religion, life, intellect, lineage, and wealth. The results indicate that although business capital assistance does not significantly affect welfare, the Zmart Program contributes to achieving holistic mustahik welfare through business mentoring and income growth, in alignment with the goals of maqāṣid al-sharī‘ah. Keywords: Productive Zakat, Business Capital Assistance, Business Mentoring,           Sales Turnover, Mustahik Welfare, Maqāṣid al-Sharī‘ah, Zmart Program.